Four new species of Monographis Attems, 1907 (Diplopoda, Polyxenida, Polyxenidae) from Vietnam - Huynh, Cuong; Veenstra, Anneke A (Zootaxa, 2022)
Four new species of penicillate millipedes from the genus Monographis Attems, 1907, collected from various regions in Vietnam, are described. They show distinctive morphological characteristics on the labrum, telotarsus, and sensilla on antennal article VI. Monographis cattienensis sp. n., M. tamdaoensis sp. n., and M. thatsonensis sp. n. belong to the group with sensilla on article VI arranged in a crescent, whereas M. konkakinhensis sp. n. is in a group with sensilla arranged in a triangle. Molecular analysis of Monographis konkakinensis sp. n., M. tamdaoensis sp. n. and M. thatsonensis sp. n. shows that these species differ genetically from other Monographis congeners. Additionally, two previously described subspecies, Monographis kraepelini malayanus Nguyen Duy-Jacquemin & Condé, 1966; and M. k. sabahnus Condé & Nguyen Duy-Jacquemin, 1984; are elevated to species, namely Monographis malayana Nguyen Duy-Jacquemin & Condé, 1966 and M. sabahna Condé & Nguyen Duy-Jacquemin, 1984.